2020
DOI: 10.1136/neurintsurg-2020-016720
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of mechanical thrombectomy and intravenous thrombolysis in atrial fibrillation associated stroke

Abstract: BackgroundAtrial fibrillation (AF) associated ischemic stroke has worse functional outcomes, less effective recanalization, and increased rates of hemorrhagic complications after intravenous thrombolysis (IVT). Limited data exist about the effect of AF on procedural and clinical outcomes after mechanical thrombectomy (MT).ObjectiveTo determine whether recanalization efficacy, procedural speed, and clinical outcomes differ in AF associated stroke treated with MT.MethodsWe performed a retrospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 27 publications
3
43
1
Order By: Relevance
“…To date, several independent factors have been identified by some authors which reportedly worsen the functional status of patients undergoing MT for stroke. These include older age, low ASPECTS scores, and high NIHSS scores [12][13][14]17,18]. In terms of the importance of age and neurological status, we have confirmed the reports of other authors; we have also gained more experience concerning the influence of a patient's clinical profile on the outcome of endovascular therapy and their post-stroke functional status in the acute period of stroke.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…To date, several independent factors have been identified by some authors which reportedly worsen the functional status of patients undergoing MT for stroke. These include older age, low ASPECTS scores, and high NIHSS scores [12][13][14]17,18]. In terms of the importance of age and neurological status, we have confirmed the reports of other authors; we have also gained more experience concerning the influence of a patient's clinical profile on the outcome of endovascular therapy and their post-stroke functional status in the acute period of stroke.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, attempts are being made to identify the parameters to determine the outcome of endovascular therapy in acute stroke patients. The most common findings are age, the patients' neurological status during the ultra-acute stage of stroke, and the ASPECTS score [12][13][14]. Atrial fibrillation, diabetes, previous exposure to anticoagulation, the morphotic parameters of blood, and inflammatory parameters all have a conflicting status in several studies [12,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 This result is further confirmed by another study performed using the multicentre Stroke Thrombectomy and Aneurysm Registry, which concluded that the presence of premorbid AF in patients who achieved good recanalisation post ET did not impact sICH rates (aOR 0.69, 95% CI 0.43 to 1.12). 16 A large 2015 multicentre retrospective analysis searched for risk factors for ICH after ET and found that AF was associated with a higher risk of ICH, but this result did not persist after adjusting for vascular risk factors. Notably, there was also no significant difference in successful recanalisation rates between those who developed sICH versus those who did not.…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, there were around 5% more cardio-embolic strokes and 2.6% less macroangiopathic strokes in the EVT alone group. While IVT might have facilitating effects in both stroke etiologies, cardio-embolic thrombi removal by EVT in the majority of cases is faster and easier compared with often hard, calcified, and plaque-associated thrombi and emboli ( 24 , 25 ). One could assume equal effects of IVT in both groups, while time to reperfusion has been shorter in the EVT alone group because of technically easier clot removals in this group requiring less passes and aspirations.…”
Section: Discussionmentioning
confidence: 99%